2017
DOI: 10.1016/j.ijpddr.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal activities of histone deacetylase inhibitors against a dipteran parasite of sheep, Lucilia cuprina

Abstract: Histone deacetylase inhibitors (HDACi) are being investigated for the control of various human parasites. Here we investigate their potential as insecticides for the control of a major ecto-parasite of sheep, the Australian sheep blowfly, Lucilia cuprina. We assessed the ability of HDACi from various chemical classes to inhibit the development of blowfly larvae in vitro, and to inhibit HDAC activity in nuclear protein extracts prepared from blowfly eggs. The HDACi prodrug romidepsin, a cyclic depsipeptide that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…In vitro cultivation of Cryptosporidium oocysts is a new method under development that can deliver deeper insights about the parasite pathophysiology and provide researchers with more precise tools to assess new drugs [8,52]. Thereon, an ex vivo ileal explant was included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro cultivation of Cryptosporidium oocysts is a new method under development that can deliver deeper insights about the parasite pathophysiology and provide researchers with more precise tools to assess new drugs [8,52]. Thereon, an ex vivo ileal explant was included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Since mocetinostat stimulates histone acetylation in tumor cells, in vivo studies have demonstrated antitumor activity and low toxicity. Phase II studies of mocetinostat are also ongoing [30]. Mocetinostat abolished leiomyosarcoma cell line (LMS) cell growth and clonogenic potential and induced apoptosis in LMS cell lines in the combined administration of mocetinostat (50mg/kg) and gemcitabine (50mg/kg) [15].…”
Section: Discussionmentioning
confidence: 99%
“…Recent work on the identification of new chemicals for blowfly control provides an illustration of both the use of the blowfly genome and the limitations of focusing solely on the sheep blowfly as a model organism for drug discovery exercises. 18 , 19 , 20 These studies reported on the potent activity of inhibitors of histone deacetylase enzymes against larval life stages of the blowfly in vitro and in vivo , hence highlighting their potential as insecticides. However, the research to date has focused solely on activity against the blowfly, with the worth of these enzymes as drug targets in other pests of animals not yet demonstrated, and hence the potential engagement of animal health companies in this area of insecticide discovery remains uncertain.…”
Section: Insecticidesmentioning
confidence: 99%